Nanocomposite hyaluronic acid-based hydrogel for the treatment of esophageal fistulas. (March 2021) - Piantanida, E.; Boškoski, I.; Quero, G.; Gallo, C.; Zhang, Y.; Fiorillo, C.; Arena, V.; Costamagna, G.; Perretta, S.; De Cola, L.
Abstract: Fistulas are abnormal connections between two body parts that can impair the quality of life. The use of biological glues represents the least invasive procedure to fill the fistula; however, it is limited by the need of multiple injections, the persistence of infection and the failure in the treatment of high-output fistulas. We describe herein the use of an injectable nanocomposite hydrogel that is able to form in situ a tissue-mimicking matrix as an innovative material for the treatment of esophageal fistulas. Injectable hydrogels that have the dual advantage of being implantable with a minimally invasive approach and of adapting their shape to the target cavity, while the introduction of mesoporous silica nanoparticles opens the possibility of drug/biomolecules delivery. The hydrogel is based on hyaluronic acid (HA), the crosslinking process occurs at physiological conditions leading to a hydrogel made of >96% by water and with a large-pore micro-architecture. The kinetic profile of the hydrogel formation is studied as a function of HA molecular weight and concentration with the aim of designing a material that is easily injectable with an endoscopic needle, is formed in a time compatible with the surgical procedure and has final mechanical properties suitable for cell proliferation. The in vivo experiments (porcine model) on esophageal-cutaneous fistulas, showed improved healing in the animals treated with the hydrogel compared with the control group. Graphical abstract: Image 1